Development of Android-Based Learning Media Using the CapCut Application in Integrated Thematic Learning in Grade IV Elementary School - Anggraini, Dini; Ningsih, Yarisda (Journal of Practice Learning and Educational Development, 2022)
This research is motivated by the limited use of interesting and easy-to-understand media that can stimulate students in learning. The purpose of this research is to determine the validity and practicality of media-based learning. Android using the CapCut. This type of research is development research (R&D) using a 4-D consisting of define, design, develop and disseminate. Given the limitations of space, time, and research costs, this research was only carried out until the develop. The subjects of this study were 3 experts and 1 fourth grade teacher and 14 fourth grade students at SDN 24 Parupuk Tabing, and 1 fourth grade teacher and 10 fourth grade students at SDN 09 Air Tawar Barat. The instruments used are expert validation sheets, teacher and student response questionnaires. The results of the study were stated to be very valid with the average value of material experts 96%, media experts 92.6% and linguists 95%. Based on the results of teacher and student responses at the research school, the percentage of the fourth grade teacher responses at SDN 24 Parupuk Tabing was 95% and the fourth grade teacher responses at SDN 09 Air Tawar Barat 90%. The percentage of student responses at SDN 24 Parupuk Tabing was 96% and student responses in grade IV at SDN 09 Air Tawar Barat were 93% and were stated to be very practical.